Citizenship in the Arab World : Kin, Religion and Nation-State - Parolin, Gianluca P. (Amsterdam University Press, 2009)
The book is the fruit of five years of on-site research on citizenship in the Arab world. It takes a broader legal perspective to the multifaceted reality of nationality and citizenship. The methodology employed builds on the interdisciplinary approach of comparative legal studies, and brings in theories, concepts and insights from anthropology, political science, Arab and Islamic studies, linguistics and sociology. The work relies on a broad range of Western and Arab references, and all sources and documents were directly accessed in their original languages; this is particularly relevant for Arab legislation (all in-text reference has been translated by the author, and the original has been inserted using scientific transliteration).
Gianluca P. Parolin deed vijf jaar lang onderzoek naar burgerschap in het Midden-Oosten. In dit boek plaatst de auteur dit begrip in een breder juridisch perspectief naar de maatstaven van de complexe realiteit van nationaliteit en burgerschap. Wetten op het gebied van nationaliteit zijn vaak gebaseerd op staten en worden als volledig soeverein beschouwd. Maar deze wetten zijn alleen effectief als rekening gehouden wordt met de culturele en juridische achtergrond van de burgers waarop ze van toepassing zijn.
English
Keywords: Sociology & anthropology; sociology; anthropology; sociologie; anthropologie